Severe post-gastric bypass hypoglycemia in pregnancy. Issue 3 (May 2022) - Schiller, Tal; Kirzhner, Alena; Zornitzki, Taiba; Cohen, Lee; Shafran, Yael Winter; Ostrovsky, Viviana; Knobler, Hilla; Vaisbuch, Edi
Abstract: Summary: Post-bariatric surgery hypoglycemia (PBH) is a serious and relatively prevalent complication of bariatric surgery and is often underdiagnosed due to unawareness. PBH can have a profound effect on health and quality of life. Data regarding the natural history and management of PBH during pregnancy are lacking. Here we describe a case of a 34-year-old woman who presented with intractable PBH during the second trimester of her third pregnancy, three years after a Roux-en-Y gastric bypass (RYGB). Treatment with nifedipine showed partial response and eventually intravenous (IV) glucose was needed until birth.